Conferences and synods in the Indian Church - Arakkal, Mons Kurian (Kanonistische Reihe, 2018)
The present study is aimed at obtaining clarity with regard to the functioning of conferences and synods in the Indian Church. Therefore, we shall critically analyse different activities of conferences and synods of three sui iuris churches, namely the Latin Church, the Syro-Malabr Church and the Syro-Malankara Church, to answer questions such as: Do they function in accordance with the common law of the Catholic Church? Do they function in accordance with the mind of the legislator? We aim lso to know how these three churches sui iuris function together to contribute for the good of the Church in India, by completely accepting and appreciating their autonomous power and at the same time keeping in mind that all the churches in the Catholic Church have equal rights. The focus of our study is to comprehend the extension of the competence of conferences and synods an their juridical status in the church